Impact of the Know-Want-Learn (KWL) Strategy on Academic Mathematics Achievements for International Students - Alsalhi, Najeh Rajeh; Taani, Osama; Arabi, Khalil Shehadeh Al; Al-Qatawneh, Sulieman; Annamalai, Nagaletchimee; Al-Tarawneh, Sabri; Eltahir, Mohd Elagzoub (Journal of International Students, 2023)
The KWL technique is a metacognitive thinking strategy that emphasises the review and application of the learner's existing knowledge. Tenth-grade students at Sharjah American International School in Sharjah, United Arab Emirates, underwent assessment using the Know-Want-Learn (KWL) strategy. This study utilised a quasi-experimental case study design and included a sample of 53 students from Sharjah American International School in the city of Sharjah. The study consisted of two groups: an experimental group of 27 individuals and a control group of 26 individuals. The control group received standard instruction, while the experimental group received KWL instruction.